حوسبة قطاع التعليم في الأردن ودوره في تحسين مستوى التعليم من وجهة نظر طلبة المرحلة الثانوية في لواء الرمثا - الزعبي، محمد يوسف (جامعة مؤتة, 2018)
This study aims to identify the role of computerization of education sector in Jordan in improving the level of education from secondary student's viewpoints in Ramtha District. The study adopted the descriptive method, applying the questionnaire in order to collect data. The sample of the study consisted of (850) male and female students at secondary grade in Ramtha which was (18%) from the study population. The results showed that there is a high role for computerization of education sector in improving education level from the point of view of secondary students in Ramtha District. Also, there are statistically significant differences in the role of computerization of education sector in Ramtha according to the gender variable to favor of the males, and for academic average to favor of weak and acceptable level. Therefore, the researcher recommends providing schools with necessary computer equipments and to train how to use them.
هدفت الدراسة التعرف إلى دور حوسبة قطاع التعليم في الأردن في تحسين مستوى التعليم من وجهة نظر طلبة المرحلة الثانوية في لواء الرمثا. واعتمدت الدراسة على المنهج الوصفي، وتم استخدام الاستبانة لجمع البيانات. وتكونت عينة الدراسة من (850) طالباً وطالبة في المرحلة الثانوية في لواء الرمثا بنسبة (18%) من مجتمع الدراسة. وأظهرت نتائج الدراسة وجود دور لحوسبة قطاع التعليم في الأردن في تحسين مستوى التعليم من وجه نظر طلبة المرحلة الثانوية في لواء الرمثا بدرجة مرتفعة، ووجود فروق ذات دلال إحصائية في دور حوسبة قطاع التعليم في الأردن في تحسين مستوى التعليم من وجهة نظر طلبة المرحلة الثانوية في لواء الرمثا تبعاً لمتغير الجنس لصالح الذكور، وتبعاً لمتغير التقدير لصالح التقدير مقبول وضعيف. وأوصي الباحث بضرورة العمل على توفير الأجهزة والأدوات المحوسبة في المدارس والتدريب على كيفية استخدامها.
Keywords: الأردن -- التعليم الثانوي -- تكنولوجيا التعليم -- الوسائل التعليمية -- التعليم الإلكتروني